A Combined Cosmogenic Nuclides Approach for Determining the Temperature‐Dependence of Erosion. Issue 4 (7th April 2022) - Dennis, Donovan P.; Scherler, Dirk
Abstract: Physical weathering in cold, steep bedrock hillslopes occurs at rates that are thought to depend on temperature, but our ability to quantify the temperature‐dependence of erosion remains limited when integrating over geomorphic timescales. Here, we present results from a 1D numerical model of in‐situ cosmogenic 10 Be, 14 C, and 3 He concentrations that evolve as a function of erosion rate, erosion style, and ground surface temperature. We used the model to explore the suitability of these nuclides for quantifying erosion rates in areas undergoing non‐steady state erosion, as well as the relationship between bedrock temperature, erosion rate, and erosional stochasticity. Our results suggest that even in stochastically eroding settings, 10 Be‐derived erosion rates of amalgamated samples can be used to estimate long‐term erosion rates, but infrequent large events can lead to bias. The ratio of 14 C to 10 Be can be used to evaluate erosional stochasticity, and to determine the offset between an apparent 10 Be‐derived erosion rate and the long‐term rate. Finally, the concentration of 3 He relative to that of 10 Be, and the paleothermometric interpretations derived from it, are unaffected by erosional stochasticity. These findings, discussed in the context of bedrock hillslopes in mountainous regions, indicate that the 10 Be‐ 14 C‐ 3 He system in quartz offers a method to evaluate the temperature‐sensitivity of bedrock erosion rates in cold, high‐alpine environments. Plain Language Summary: All mountains erode, but not all mountains erode in the same way and at the same rate. In cold mountainous landscapes, temperature is thought to be an important control on erosion. Previous research suggests that rocks fracture by frost most effectively at temperatures between −3°C and −8°C, and that the warming and thawing of permanently frozen ground (permafrost) destabilizes hillslopes and leads to more and larger rockfalls. However, our ability to test these hypotheses is limited, due to difficulties in measuring or estimating erosion rates and linking them with the temperatures that rocks experience. In this paper we present the results of a computer modeling study that tests the suitability of geochemical tools as measures of erosion rate, erosion style, and long‐term bedrock temperature. We find that these geochemical tracers, called cosmogenic nuclides, can be used to determine erosion rates, even in places that are prone to rare rockfalls, together with the long‐term bedrock temperature. They are therefore uniquely suitable for evaluating the link between temperatures and erosion rates in cold bedrock hillslopes over long timescales. Key Points: Cosmogenic 10 Be, 14 C, and 3 He is used to determine erosion rates, erosion styles, and bedrock temperatures in cold regions 14 C/ 10 Be ratios of surface samples reflect the depth at which material was previously eroded, allowing for determination of erosion style 14 C/ 10 Be ratios combined with 10 Be‐derived erosion rates improve erosion rate estimates in stochastically eroding environments